POLICY IMPLEMENTATION DISTRIBUTION OF FUNDS TO ASSIST STUDENT EDUCATION COSTS IN NORTH MOROWALI REGENCY - Telly Anggreani; Intam Kurnia; Munari (RADJA PUBLIKA, 2025)
Tuition assistance for students as a form of financial support from the Regional Government through the Kesra section of the Morut Regency Secretariat, to ease the burden of tuition fees, and improve the quality of Human Resources (HR). Problems faced in the implementation of the program policy, namely delays in disbursement of aid funds, lack of adequate socialization and information, and weak coordination between related parties. The research method used is a qualitative method, with data collection techniques namely observation, interviews, and documentation, and data analysis used is an interactive model. The results of the study, namely the communication aspect carried out by the Kesra section of the Morut Regency Secretariat has used various media to convey information, both manually and online, but currently many still use manual methods. In the aspect of Resources, the amount of assistance depends on the size of the APBD, the employees of the Kesra section and the Verification Team, already have good competence but the number of personnel is still minimal. In addition, the disposition aspect between related parties has been neutral, transparent, and accountable but there are limitations in the information system. The aspect of bureaucratic structure, still faces administrative and technical challenges that require serious attention. In conclusion, the implementation of the BBP program for students in Morut Regency has been effective in substance, but not yet fully efficient technically. Therefore, improvements to the funding mechanism are needed to ensure the program's speed, effectiveness, and sustainability.